Urinary tract infection and indwelling urinary catheters: prospective study in gynecological surgery with antibiotic prophylaxis - Carraro-Eduardo, José Carlos (2015)
CONTEXT AND OBJECTIVES: Urinary tract infections are the most common cause of hospital-acquired infections, and the use of indwelling urinary catheters is a predisposing factor for their development. The aims of this study were to estimate the frequency of pre and postoperative bacteriuria, identify the microorganisms involved, count the colony-forming units, determine the antibiotic sensitivity profile and compare the results from pre and postoperative urinalyses among women undergoing gynecological surgery with implantation of a urinary catheter. DESIGN AND SETTING: Non-controlled prospective observational single-cohort epidemiological study carried out at a university hospital. METHODS: Urine samples were collected before and 24 hours after catheterization for urinalysis, cultur-ing and antibiotic sensitivity testing. Pre and postoperative urinalyses were compared using Wilcoxon and McNemar non-parametric tests. RESULTS: Fifty-one women participated in the study. Escherichia coli grew in six preoperative samples (11.8%) and Klebsiella pneumoniae in one (1.9%), but bacterial growth did not occur in any postopera-tive sample. Urinalysis showed lower number of pus cells in the postoperative urine samples (P < 0.05). There were no differences in red blood cell counts or in the nitrite and leukocyte esterase tests, between the samples. CONCLUSION: Bacteriuria was found in 13.7% of the preoperative samples. Gram-negative bacteria sensi-tive to most antibiotics were identified. In the postoperative samples, no bacterial growth was observed. Urinalysis only showed significant reduction of leukocyturia in the postoperative period.